(untitled) (Perioperaciina Medicina, 2019)
Background. Burn injury, as one of the most common types of trauma, requires a comprehensive approach to treatment, including surgical and conservative treatment with effective post-burn wound protection. One of the main obstacles to wound healing is purulent-infectious complications, for prevention of which antiseptics are widely used. The aim is to study the microbiological, histological features of the wound healing course in the acute period of burn disease with the use of various antiseptics. Materials and methods. In the research there were involved 44 patients with burns (burn area 10–20 % of the body surface), treated in the Clinical Center for Thermal Injury and Plastic Surgery of Communal Non-Commercial Enterprise “Vinnytsia Regional Clinical Hospital named after M. I. Pirogov” (2018–2019). Depending on the antiseptic therapy, these patients were divided into three observation groups. Patients in the 1st study group (n = 15; mean age 48.07 ± 12.05 years) were treated with 2.0 % povidone-iodine during dressing. In the 2nd group (n = 15; mean age – 48.53 ± 14.76 years) antiseptic based on 0.02 % decamethoxin was used. In patients of the comparison group (n = 14; mean age – 47.71 ± 12.39 years) a solution of 10.0 % NaCl was administrated for topical wound management. Microbiological assessment of the condition of the wound surface (on 3, 7, 14, 21 days) and histological examination of tissue samples from the bottom of the wound (on 3, 7, 14 days) were carried out by means of standard methods. Results. Under the use of antiseptic agents based on 2.0 % povidone-iodine and 0.02 % decamethoxin during the treatment period in patients with burns up to 14 days, an effective reduction in the number of conditionally pathogenic microorganisms on the wound surface to lg (4.8 ± 0.4) and lg (3.06 ± 0.5) CFU/ml, respectively, was registered and it was significantly 1.5 times lower than that based on 10 % sodium chloride solution (p < 0.05). When applying decamethoxin for 14 days at the same time as the eradication of conditionally pathogenic microorganisms, moderate colonization of wounds was registered by representatives of normal skin microbiota (Corynebacterium spp., S. epidermidis). Histologically, there was found that with the use of 2.0 % povidone-iodine, the wound healing course was accompanied by a marked decrease in inflammation signs, as well as a pronounced inhibition of the formation of granulation tissue (10–14 days). The use of 0.02 % decamethoxin was accompanied by the formation of granulation tissue of sufficient maturity for atodermoplasty, in the presence of signs of inflammatory cellular reaction with the presence in the superficial parts of the bottom of the post-burn wounds of the fibrinoid layer, with signs of permanent formation of new hemocapillaries in it, surrounded by a thin argyrophilic mesh. When using a hypertonic sodium chloride solution before autodermoplasty, the granulation tissue had signs of uneven inflammatory cell infiltration. Signs of leukocyte-necrotic tissue changes, fibrinoid-leukocyte layers with fragments of tissue detritus, signs of resuscularization of granulation tissue were recorded. Conclusion. Microbiological data strongly suggest the efficacy of 0.02 % decamethoxin and 2.0 % povidone-iodine in reducing microbial wound colonization infection compared to 10.0 % NaCl. The use of antiseptics and hypertonic sodium chloride solution in the acute period of burn disease provides a marked reduction in histological signs of inflammation in the wound with a noticeable positive effect of decamethoxin and 10.0 % NaCl on the formation of granulations and their revascularization compared with povidone-iodine (p < 0.001).